2007
DOI: 10.1111/j.1750-3841.2006.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protective Agents on the Viability of Geotrichum candidum during Freeze‐Drying and Storage

Abstract: The effect of 3 cryoprotective agents (trehalose, sucrose, and maltose) on the survival of concentrated cultures of Geotrichum candidum was studied. Initially, the effect of the carbohydrates at 9% and 23% concentrations or combined with skim milk (16%) was compared to the control (skim milk alone) immediately after freeze-drying. Two freeze-drying shelf temperatures, 25 degrees C and 35 degrees C, were investigated. Afterwards, the survival of G. candidum freeze-dried with carbohydrates at 23% concentration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…The combination of mannitol with sodium caseinate appeared useful to increase T g of the mixture due to the high T g of sodium caseinate. A similar study showed that incorporation of skim milk into disaccharides increased T g of freeze-dried Geotrichum candidum (Hamoudi et al, 2007). In our study, no T g of pure crystalline mannitol (at 10°C) was detected, indicating that mannitol strongly interacted with other substances (Kalichevsky and Blanshard, 1992;Taylor and Zografi, 1998).…”
Section: Glass Transition Temperature and Residual Moisture Content Osupporting
confidence: 59%
“…The combination of mannitol with sodium caseinate appeared useful to increase T g of the mixture due to the high T g of sodium caseinate. A similar study showed that incorporation of skim milk into disaccharides increased T g of freeze-dried Geotrichum candidum (Hamoudi et al, 2007). In our study, no T g of pure crystalline mannitol (at 10°C) was detected, indicating that mannitol strongly interacted with other substances (Kalichevsky and Blanshard, 1992;Taylor and Zografi, 1998).…”
Section: Glass Transition Temperature and Residual Moisture Content Osupporting
confidence: 59%
“…However, when this method was employed for drying probiotic bacteria and other cells, undesirable effects such leakage of the cell membrane due to changes in the physical state of membrane lipids or changes in the structure of sensitive proteins in the bacteria cell occur (Leslie, Israeli, Lighthart, Crowe, & Crowe, 1995;Teixeira, Castro, & Kirby, 1996;Teixeira, Castro, Malcata, & Kirby, 1995). Protective solutes such as cryoprotectants (saccharides and polyols) and other compatible solutes like adonitol, betaine, glycerol and skim milk were used to increase bacteria's viability and increase their survival during freeze-drying and subsequent storage (de Valdez, Degiori, Holgado, & Oliver, 1983;Hamoudi, Goulet, & Ratti, 2007;Selmer-Olsen, Birkeland, & Sorhaug, 1999). These studies lead to the conclusion that the effect of each protective agent on the viability of a specific LAB strain during or following the freeze-drying process have to be determined on a case-bycase basis (Carvalho et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A number of factors, such as temperature, atmosphere, exposure to light and moisture influence the viability of freeze-dried cultures [16]. It is well established that cryoprotectants are almost indispensable when freezing and drying microorganisms, but the contribution of these compounds to stability of dried microorganisms during storage is discussed [17]. The disadvantages of dried cultures undermine their application, but advantages can outweigh disadvantages if the inactivation during storage can be more clearly understood and consequently reduced.…”
Section: Introductionmentioning
confidence: 99%